2011
DOI: 10.3390/polym3042142
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Treated Multi-Walled Carbon Nanotubes (MWCNTs) for Epoxy Nanocomposites

Abstract: Plasma nanocoating of allylamine were deposited on the surfaces of multi-walled carbon nanotubes (MWCNTs) to provide desirable functionalities and thus to tailor the surface characteristics of MWCNTs for improved dispersion and interfacial adhesion in epoxy matrices. Plasma nanocoated MWCNTs were characterized using scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), surface contact angle, and pH change measurements. Mechanical testing results showed that epoxy reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…It was found that the surface morphology of the samples had changed with a thin layer of compound (~ 1 nm) wrapped on the outer surfaces of biopolymeric MWSB nanocomposites. This observation was consistent with the previous finding reported earlier by a team working on plasma-coated MWCNT 44 . According to the HR-TEM analysis, they observed a layer of thick amorphous plasma nano-coated on the MWCNT surfaces when compared to the uncoated MWCNT.…”
Section: Resultssupporting
confidence: 94%
“…It was found that the surface morphology of the samples had changed with a thin layer of compound (~ 1 nm) wrapped on the outer surfaces of biopolymeric MWSB nanocomposites. This observation was consistent with the previous finding reported earlier by a team working on plasma-coated MWCNT 44 . According to the HR-TEM analysis, they observed a layer of thick amorphous plasma nano-coated on the MWCNT surfaces when compared to the uncoated MWCNT.…”
Section: Resultssupporting
confidence: 94%
“…COOH-functionalized Au-decorated MWCNTs were obtained from McGill University, Canada, and diluted with d 2 H 2 O to a working concentration of 18–20 mg/L prior to conjugation, to ensure mono-dispersity. COOH functionalization was achieved by plasma treatment, a general method for the addition of functional groups at defects in graphene structures [ 36 , 37 ]. Au decoration was carried out by pulsed laser ablation using a Nd:YAG laser focused on the MWCNT target at a fluence on the order of 1 J/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…However, small signal-to-noise ratio with our current technique gave technical difficulties as similarly observed in Ref. [13]. The confirmation of the functional groups still needs to be worked in the future with other diagnostic techniques.…”
Section: Resultsmentioning
confidence: 72%